Haptic Addition to a Visual Menu Selection Interface Controlled by an In-Vehicle Rotary Device. (14th February 2012) - Grane Grane, Camilla Camilla; Bengtsson Bengtsson, Peter Peter
Abstract : Today, several vehicles are equipped with a visual display combined with a haptic rotary device for handling in-vehicle information system tasks while driving. This experimental study investigates whether a haptic addition to a visual interface interferes with or supports secondary task performance and whether haptic information could be used without taking eyes off road. Four interfaces were compared during simulated driving: visual only, partly corresponding visual-haptic, fully corresponding visual-haptic, and haptic only. Secondary task performance and subjective mental workload were measured. Additionally, the participants were interviewed. It was found that some haptic support improved performance. However, when more haptic information was used, the results diverged in terms of task completion time and interface comprehension. Some participants did not sense all haptics provided, some did not comprehend the correspondence between the haptic and visual interfaces, and some did. Interestingly, the participants managed to complete the tasks when using haptic-only information.